2022
DOI: 10.1002/jcu.23188
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time three‐dimensional echocardiography and two‐dimensional speckle tracking imaging in the evaluation of left atrial function in patients with triple‐vessel coronary artery disease without myocardial infarction

Abstract: Objective To evaluate left atrial function in patients with triple‐vessel disease (TVD) without myocardial infarction by real‐time three‐dimensional echocardiography (RT‐3DE) and two‐dimensional speckle tracking imaging (2D‐STE). Methods Sixty patients with coronary artery disease (CAD) without myocardial infarction were classified into two groups in accordance with the coronary angiography results: group B (all triple‐vessel stenosis ≥ 50% and < 75%) and group C (all triple‐vessel stenosis ≥ 75%). Thirty heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
2
1
Order By: Relevance
“…Yukari et al [22] demonstrated that all phasic LA functions containing booster pump function significantly declined in patients with HCM compared with the healthy group. Other researchers considered LA booster pump function as a compensatory mechanism for the LVEF via enhancing LAAEF and contraction strain; in their study, HCM patients had lower reservoir and conduit function while having enhanced pump function in comparison with the control group [23,24]. Nevertheless, the LA contraction function in our research did not show a difference between the control group and HCM patients, whether preoperative or postoperative.…”
Section: Discussioncontrasting
confidence: 64%
“…Yukari et al [22] demonstrated that all phasic LA functions containing booster pump function significantly declined in patients with HCM compared with the healthy group. Other researchers considered LA booster pump function as a compensatory mechanism for the LVEF via enhancing LAAEF and contraction strain; in their study, HCM patients had lower reservoir and conduit function while having enhanced pump function in comparison with the control group [23,24]. Nevertheless, the LA contraction function in our research did not show a difference between the control group and HCM patients, whether preoperative or postoperative.…”
Section: Discussioncontrasting
confidence: 64%
“…The results showed that the 3-dimensional ultrasound parameters indicating storage function and conduit function (RAVImax, RAPEF) and 2D-STE parameters (RASRs, RASRe) showed the same trend in Group C. Although the pump function (RAAEF, RASRa) did not show a consistent trend in this study, a positive correlation between the 2 was known in previous studies. [ 41 ] It further suggests that speckle tracking parameters are more sensitive and that 2D-STE has advantages over conventional echocardiography in evaluating right atrial function.…”
Section: Discussionmentioning
confidence: 99%
“…Also, strain rate measurements show a reduced load dependence. In addition, they have low interobserver variabilities and are not susceptible to respiratory movements or heartbeat [ 34 , 49 , 54 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Speckle Tracking Echocardiographymentioning
confidence: 99%